Norwegia wobec Bloku Wschodniego na tle wydarzeń roku 1968 w Czechosłowacji - Romański, Mirosław (Acta Universitatis Lodziensis. Folia Historica, 2014)
The primary objective of the article is the discussion of the most important aspects, policy directions and the attitude of Norway towards the events in Czechoslovakia 1968. It is a very interesting matter because Norway was a country that reacted in the most negative way to these events. None of the researches have deeply analysed that problem so far, and the archival documentation is rich in lots of unknown facts. The text is of the exiguous mature and was written on the basis of the bulletins of the Ministry of the Foreign Affairs of People’s Republic of Poland, and also the archived sources coming from the Department of the Central Committee of the Polish United Workers Party. Due to the that data coming from these sources have not been published so far, the article has shed new light on the current knowledge status in the subject considered.